Accelerated oxidation of the emerging brominated flame retardant tetrabromobisphenol S by unactivated peroxymonosulfate: The role of bromine catalysis and formation of disinfection byproducts. (1st October 2021) - Xu, Haiyan; Meng, Liang; Zhao, Xulei; Chen, Jing; Lu, Junhe; Chovelon, Jean-Marc; Ji, Yuefei
Highlights: TBBPS was efficiently oxidized by unactivated PMS. Oxidation of TBBPS by unactivated PMS exhibited an autocatalytic performance. HOBr was the critical reactive species responsible for the autocatalysis. Products resulted from β-scission, debromination, and cross-coupling reactions. Br-DBPs, including CHBr3, DBAA, and MBAA, were detected during TBBPS oxidation. Abstract: Tetrabromobisphenol S (TBBPS) is an emerging brominated flame retardant (BFR) that can cause endocrinological abnormalities in aquatic species and is neurotoxic and cytotoxic to humans. Herein, we investigated the oxidation of TBBPS by unactivated peroxymonosulfate (PMS) in aqueous solution. Results show that PMS was capable of oxidizing TBBPS without activation, and the transformation of TBBPS was pH-dependent. Interestingly, the unactivated PMS oxidation of TBBPS exhibited an autocatalytic behavior. Radical quenching experiments and electron paramagnetic resonance (EPR) analyzes ruled out the involvement of hydroxyl radical (HO) and sulfate radical (SO4 ‑ ) as reactive species. While the generation of singlet oxygen ( 1 O2) was confirmed in PMS solution, it was also not responsible for TBBPS oxidation. The bromine substituents are believed to be responsible for the autocatalysis observed during PMS oxidation. We propose that the initial oxidation of TBBPS by PMS resulted in the release of bromide ions (Br − ) via debromination, which could be rapidly oxidized to hypobromous acid (HOBr). 3, 5-Dimethyl-1 H -pyrazole (DMPZ) trapping coupled with liquid chromatography-mass spectrometry (LC-MS) analysis evidenced the formation of HOBr in PMS/TBBPS system. Therefore, the presence of Br −, albeit at trace level, could significantly accelerate the oxidation of TBBPS in PMS solution via HOBr formation. The intermediate products of TBBPS were identified by solid phase extraction (SPE) coupled with high resolution-mass spectrometry (HR-MS). The oxidation of TBBPS by unactivated PMS was likely initiated through a single electron transfer mechanism, and the transformation pathways included β-scission, debromination, and cross-coupling reactions. Further oxidation and ring-opening of the intermediates yielded three brominated disinfection byproducts (Br-DBPs), including bromoform (CHBr3 ), mono-, and di-bromoacetic acids (MBAA and DBAA), as quantified by gas chromatography (GC). The presence of natural organic matter (NOM) inhibited the oxidation of TBBPS and reduced the yields of Br-DBPs. Our results indicate that unactivated PMS was efficient in the abatement of TBBPS in aqueous solution due to the accelerated oxidation by bromine catalysis; however, the formation of brominated intermediate products and Br-DBPs should be scrutinized due to their potential carcinogenicity and mutagenicity. Graphic abstract: Image, graphical abstract